Estudio de factibilidad para la creación de la empresa Canajo S.A.S. dedicada a la confección de uniformes escolares en la ciudad de Armenia (2015)
A feasibility study for the creation of a clothing company in the city of Armenia, in order to establish new sources of employment contributing to the decline in unemployment in the city, under the name SAS specialized in CANAJO performed manufacture and distribution of school uniforms. Initially a market study was conducted to determine the target population, demand, supply, sale prices and determine the distribution channels and marketing. Subsequently, the technical study of the project that helped to determine the size of the project was conducted, the location and distribution of plant production and sales area, the process of making goods and supplies required for production